Estudo químico e biológico de micro-organismos endofíticos associados às frutas banana, pêra e goiaba - Medeiros, Lívia Soman de (Universidade Federal de São Carlos, 2010)
Studies about interaction between microorganisms and plants are focused mainly in the vegetal tissues like roots, steam and leaves. Fruits are a right target for microorganism attacks. Nevertheless, endophytic microorganisms isolated from fruits, seems to be not so explored in chemical point of view. Thus, in this work, it was developed the chemical study about the metabolism referred to endophytic microorganisms from edible fruits, commonly consumed in Brazil: banana, pear, apple and guava fruit. Through HPLC/UV analysis, it were realized and compared, the isolated microorganisms metabolic development, in different media cultures. It was included the media with the proper host fruits. The indolic alkaloid n-acetiltryptamine was isolated from a extract of the bacteria associated to the pear fruit (BP1). From the extracts of guava fruit endophytic fungus, Cladosporium uredinicola (FG1), it were isolated four new depsides in literature: 3-hidroxi-2,5-dimetilfenil 2,4-diidroxi-3,6-dimetilbenzoate (D1), 3-hidroxi-2,4,5-trimetilfenil 2,4-diidroxi-3,6-dimetilbenzoate(D2), 3-hidroxi-2,5- dimetilfenil 3-[(2,4-diidroxi-3,6-dimetilbenzoatoil)oxi]-6-hidroxi-2,4-dimetilbenzoate (D3) e 3-hidroxi-2,4,5-trimetilfenil 3-[(2,4-diidroxi-3,6-dimetilbenzoatoil)oxi]-6- hidroxi-2,4-dimetilbenzoate (D4). The identification of these metabolites was performed according to the respective data from RMN 1 D and 2D, and MS of high and low resolution. It was checked the MIC intervals of D1, D3 and D4 against five tested bacteria. It was realized the bactericide activity of D1 in a concentration of 25μg/mL against Pseudomonas aeruginosa and Bacillus subtilis. It was also verified the photosynthesis inhibitory activity of depsides D1 and D3 produced by the fungus. The fungus C.uredinicola, showed a great depsides production ability. However, this production showed signifcants alterations when fenolic substrates were given to the fungus, in a usual culture media. The estimative of D3 and D4 production curve was also established. The LC-MS/MS technique use, allowed the selective depsides D3 and D4 detection in guava fruit extract, in low concentration ranges.
Chemical study of the secondary metabolites produced by endophytic microorganisms isolated from banana, pear and guava fruit
Keywords: Química orgânica; Microorganismos endofíticos; Frutas; Metabólitos secundários; Depsídeos; CIENCIAS EXATAS E DA TERRA::QUIMICA